THE KNOWLEDGE RELATIONSHIP ABOUT ELDERLY POSYANDU WITH THE MOTIVATIONS OF THEMSELVES TO ATTEND THE ELDERLY POSYANDU AT CANDI KARANGNONGKO - Desi Susanti; Agus Kirwanto; Witriyani . (STIKES DUTAGAMA KLATEN, 2015)
Background : The number of the elderly people in Indonesia in 2011 is about 24 million peoples or nearly 10 percent of the population. In fact in 1970 there were only 2 million peoples. For 40 years, the increasing of the elderly 10-fold while the population only increased 2-fold (Kompas, 2012). The developing of elderly population need a special attentions especially how to develop the quality of their line this has aim to keep their healthy. Elder posyandu works as well as the aim, will give chance opportunity for elder to get well health service. So they live will keep well and maximal. For the elder must use this opportunity of the program as well probably their healthy will keep cared and showed by the health worker (Wahono, 2010). The knowledge of elder when they know this program will influence their motivation to join in this program (Ismawati, 2010). So very important to develop their knowledge for the benefit of join in elder program for make their live motivate to join it. Purpose : to determine the relationship of the knowledge about elderly with their motivation to attend elderly posyandu at Candi Karangnongko. Methods : The method of the study is Analytic correlation with cross sectional design and the object of the study is elderly people at Candi Karangnongko. The sampling techniques using non-probability sampling technique with a kind of saturation sampling, it means that sampling by taking all the members of the population which are being sampled. Results : The elderly knowledge about elderly posyandu at Candi Karangnongko is quite enough, it’s about 20 peoples (50,0%) . The motivations of the elderly to attend elderly posyandu at Candi Karangnongko is high, it’s about 35 people (87,5%).